Impact of Obesity and Knee Osteoarthritis on Morbidity and Mortality in Older Americans - Losina, Elena (2011)
BACKGROUND: Obesity and knee osteoarthritis are among the most frequent chronic conditions affecting Americans aged 50 to 84 years. OBJECTIVE: To estimate quality-adjusted life-years lost due to obesity and knee osteoarthritis and health benefits of reducing obesity prevalence to levels observed a decade ago. DESIGN: The U.S. Census and obesity data from national data sources were combined with estimated prevalence of symptomatic knee osteoarthritis to assign persons aged 50 to 84 years to 4 subpopulations: nonobese without knee osteoarthritis (reference group), nonobese with knee osteoarthritis, obese without knee osteoarthritis, and obese with knee osteoarthritis. The Osteoarthritis Policy Model, a computer simulation model of knee osteoarthritis and obesity, was used to estimate quality-adjusted life-year losses due to knee osteoarthritis and obesity in comparison with the reference group. SETTING: United States. PARTICIPANTS: U.S. population aged 50 to 84 years. MEASUREMENTS: Quality-adjusted life-years lost owing to knee osteoarthritis and obesity. RESULTS: Estimated total losses of per-person quality-adjusted life-years ranged from 1.857 in nonobese persons with knee osteoarthritis to 3.501 for persons affected by both conditions, resulting in a total of 86.0 million quality-adjusted life-years lost due to obesity, knee osteoarthritis, or both. Quality-adjusted life-years lost due to knee osteoarthritis and/or obesity represent 10% to 25% of the remaining quality-adjusted survival of persons aged 50 to 84 years. Hispanic and black women had disproportionately high losses. Model findings suggested that reversing obesity prevalence to levels seen 10 years ago would avert 178 071 cases of coronary heart disease, 889 872 cases of diabetes, and 111 206 total knee replacements. Such a reduction in obesity would increase the quantity of life by 6 318 030 years and improve life expectancy by 7 812 120 quality-adjusted years in U.S. adults aged 50 to 84 years. LIMITATIONS: Comorbidity incidences were derived from prevalence estimates on the basis of life expectancy of the general population, potentially resulting in conservative underestimates. Calibration analyses were conducted to ensure comparability of model-based projections and data from external sources. CONCLUSION: The number of quality-adjusted life-years lost owing to knee osteoarthritis and obesity seems to be substantial, with black and Hispanic women experiencing disproportionate losses. Reducing mean body mass index to the levels observed a decade ago in this population would yield substantial health benefits. PRIMARY FUNDING SOURCE: The National Institutes of Health and the Arthritis Foundation.